Apakah Literasi Keuangan Memperkuat Pengaruh Program Tabungan Emas dan Adopsi Fintech terhadap Minat Menabung UMKM? - Natania, Talitha; Putra, Iwan; Ramalia, Aminah (Magister Ilmu Akuntansi Universitas Jambi, 2026)
This study aims to analyze the effect of the implementation of the Pegadaian Gold Savings Program and fintech adoption on the saving intentions of Micro, Small, and Medium Enterprises (MSMEs), as well as to examine the role of financial literacy as a moderating variable. This research employs a quantitative approach using a survey method by distributing questionnaires to 160 MSME respondents in Jambi City. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that fintech adoption has a positive and significant effect on saving intentions, while the implementation of the Pegadaian Gold Savings Program does not have a significant effect. Financial literacy is also found to have a positive and significant effect on saving intentions. Furthermore, financial literacy significantly moderates the relationship between fintech adoption and saving intentions, but does not significantly moderate the relationship between the implementation of the Pegadaian Gold Savings Program and saving intentions. These findings indicate that improving financial literacy is essential in enhancing the effectiveness of fintech utilization in increasing MSMEs’ saving intentions. The implications of this study are expected to provide insights for policymakers and financial institutions in developing strategies to improve financial literacy and optimize the use of fintech and gold savings products among MSMEs.